PENERAPAN EXTREME PROGRAMMING DALAM MEMBANGUN APLIKASI KOS-KOSAN DI KOTA SUKABUMI BERBASIS WEB - Ali Fardiansyah, Naufal; Iwan Rizal Setiawan; Lelah Lelah (STEKOM PRESS, 2023)
With the changing times, technology has become more sophisticated and powerful. Even all circles of society also feel the impact, as time goes by many people have taken advantage of this technology, thus making it easier for users to carry out activities in each of their activities. Especially in this millennial era, which predominantly uses everything digital. For example, new students who study to the next level at a dominant university from outside the region who need a temporary residence or what is commonly called a boarding house. The difficulty encountered at first was the difficulty of getting information and locations that were easily accessible by students to campus. In this way researchers take advantage of existing problems by utilizing technology to create an information system. With this application, it is hoped that it will make it easier for students to find boarding houses that match the student's wishes and assist the owner of the boarding house in promoting his boarding house. By making this boarding house application, it is a form of utilizing existing technology so that it can be used anywhere and anytime. By using this extreme programming method, it is software development that gives users access rights to add or change application processes. So a website was created to build applications for boarding houses in the city of Sukabumi.